Proceedings of the 40th International Conference on Software Engineering: Software Engineering in Society 2018
DOI: 10.1145/3183428.3183434
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization of swedish government agencies

Abstract: So ware engineering is at the core of the digitalization of society. Ill-informed decisions can have major consequences, as made evident in the 2017 government crisis in Sweden, originating in a data breach caused by an outsourcing deal made by the Swedish Transport Agency. Many Government Agencies (GovAgs) in Sweden are rapidly undergoing a digital transition, thus it is important to overview how widespread, and mature, so ware development is in this part of the public sector. We present a so ware development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…When procuring a new digital system, such as an EHR, requirements related to HCI and ergonomics are often either completely lacking or expressed in unverifiable terms [7]. Borg et al [62] showed that, in procuring digital tools, authorities primarily focus on functional requirements (what the system should do) rather than on quality demands (how well the functions are supported) such as usability. On the software development side, functional requirements are prioritized over quality-related requirements [63].…”
Section: Path 2: Generic Requirement Formulationsmentioning
confidence: 99%
“…When procuring a new digital system, such as an EHR, requirements related to HCI and ergonomics are often either completely lacking or expressed in unverifiable terms [7]. Borg et al [62] showed that, in procuring digital tools, authorities primarily focus on functional requirements (what the system should do) rather than on quality demands (how well the functions are supported) such as usability. On the software development side, functional requirements are prioritized over quality-related requirements [63].…”
Section: Path 2: Generic Requirement Formulationsmentioning
confidence: 99%
“…Although the highlighted difficulties persist, there are many PA project management initiatives that use the Agile methodologies, e.g., in the software development Census of the Swedish Government Agencies, the majority of Government Agencies consider their approach to be more Agile than planned [195], [196]. In addition to Barcelona and Chicago, mentioned in Section III-D, the Agile methodologies are applied in several PAs [17], [149], ranging from National (e.g.…”
Section: A Change Managementmentioning
confidence: 99%
“…Due to Industry 4.0, digitalization has played a key role in the development of all business areas (Borg et al, 2018(Borg et al, , 2020Drath and Horch, 2014;Szela ˛gowski and Berniak-Wo zny, 2024). It characterizes the way in which organizations are changing their processes and practices to comply with the requirements of the new era.…”
Section: Introductionmentioning
confidence: 99%
“…Digitalization refers to comprehensive organizational development and process support (Almeida et al, 2020;Borg et al, 2018;Bouwman et al, 2019;Hammer, 1990). Thus, it does not simply entail automating existing practices, digitizing information, or using IS to change the nature of specific tasks (e.g.…”
Section: Introductionmentioning
confidence: 99%